Building Motivation In Learning For Academic Success - Wilda Deliana Harahap; Herman Nirwana; Neviyarni S (Journal Of Psychology, Counseling And Education, 2024)
The purpose of this study is to investigate the role of motivation in students' learning process. Motivation is considered a dominant factor in achieving learning outcomes, although intelligence and aptitude also play an important role. This research aims to understand the relationship between motivation and learning outcomes, assuming that highly motivated individuals will achieve better learning outcomes. The research method used is a literature study or literature review. Literature review involves searching various sources such as books, journals and publications related to motivation and learning. Motivation plays an important role in driving and guiding individual behaviour in learning. Motivation can come from extrinsic and intrinsic factors.